Olivia or The weight of the past - Rossner, Judith (Crown, 1994)
Not interested by college, influenced by her Italian maid, Caroline heads for Italy, where she gets pregnant by a restauranteur, gives birth to Olivia and learns cooking. She leaves him, returns to New York and makes a bomb as a gourmet cook. By the author of Looking for Mr. Goodbar.